A Study of Prospective Local Own-Source Revenues in Central Mamuju, Indonesia - Andi Lukman Irwan; Haryanto Haryanto; Muhammad Chaeroel Ansar (Department of Government Studies Universitas Muhammadiyah Makassar, 2022)
The local own-source revenues is crucial to be addressed. This study aims to provide an overview of the taxes and levies revenue and analyzes prospective local own-source revenues in Central Mamuju Regency. It uses primary and secondary data collected with direct observation in the field of research, literature study, in-depth interview, and focus group discussions (FGD) with stakeholders. The observation and literature study took place on several objects of taxes and levies: ten items of tax and eight items of retribution. Furthermore, the in-depth interview and online FGD were conducted. As a result, the potential for revenue from regional taxes and levies in Central Mamuju Regency is still more significant compared to the targets and realizations that the Central Mamuju government has initiated. Therefore, other potentials have not been optimized as a source of regional income. For instance, terminal retribution, market retribution, and waste retribution, after an in-depth study, the actual amount of potential is greater than the target set by the local government and the realization that has been achieved. Therefore, it requires more attention from the government to optimize the existing potential to increase local revenue.